Some Aspects of an Undirected Graph on a Finite Subset of Natural Numbers - Pranab Kalita (International Journal of Advanced Science and Technology, 2020)
In this paper, we investigate some special properties of the undirected graph , defined in [1], on a finite subset of natural numbers. We also determine various properties of , the complement of .